The effect of foreign entry and ownership structure on the Philippine domestic banking market - Unite, Angelo A; Sullivan, Michael J (Journal of Banking & Finance, 2003)
We examine the response of domestic Philippine banks to the relaxation of foreign entry regulations that occurred in the Philippines. We find evidence that foreign bank entry is associated with a reduction in interest rate spreads and bank profits, but only for those domestic banks that are affiliated to a family business group. Foreign entry corresponds more generally with improvements in operating efficiencies, but a deterioration of loan portfolios. Overall, we conclude that foreign competition compels domestic banks to be more efficient, to focus operations due to increased risk, and to become less dependent on relationship-based banking practices.